Improving Empathy And Social Attitudes Of Early Childhood Through The Storytelling Method - Sri Yatimah; Ibadullah Malawi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Empathy and social attitudes are essential components in the social-emotional development of early childhood. However, the results of initial observations in Group A of ABA 1 Kindergarten, Madiun City showed that both aspects of these attitudes were still low, reflected in the lack of concern and cooperation of children. This study aims to describe the implementation and test the effectiveness of the storytelling method as a pedagogical intervention to improve these attitudes. The type of research used was Classroom Action Research (CAR) involving 14 children of Group A of ABA 1 Kindergarten, Madiun City as subjects. This study was conducted in two cycles (Cycle I and Cycle II). Data collection used observation and questionnaires. Data analysis was carried out descriptively quantitatively by calculating the percentage of average achievement of attitudes. The criteria for success of the action were determined if the average percentage reached the High category (minimum 70%). The achievement of empathy and social attitudes showed a significant increase. At the Pre-Cycle stage, the achievement of empathy was 44% and social attitudes 46% (Low Category). Following improvements in Cycle II, which emphasized children's active interaction in the story, achievement increased sharply, reaching 77% for empathy and 78% for social attitudes. These figures exceeded the established success criteria. The application of interactive and contextual storytelling has proven effective in improving empathy and social attitudes in Group A early childhood children at ABA 1 Kindergarten in Madiun City. This method is recommended for continued use in stimulating social-emotional development in early childhood education settings